Influenza antiviral: Oseltamivir / Nur Nadrah Mat Supri - Mat Supri, Nur Nadrah (Faculty of Pharmacy, 2023)
The Disease Control Division of the Malaysian Ministry of Health (MOH) recently held a discussion on the current state of influenza cases in the country. They have concluded that the antiviral Oseltamivir should be prescribed as soon as possible to the high-risk group to prevent the worsening of influenza-like illness (ILI) and to reduce hospitalization. The high-risk populations that should be thoroughly evaluated and considered to be prescribed with Oseltamivir include: 1. individuals with chronic respiratory diseases including asthma, chronic obstructive pulmonary disorder (COPD), and obstructive sleep apnea 2. pregnant women or 2 weeks post-natal women (Pregnancy category: C) 3. obese individuals with body mass index (BMI) of more than 40 4. individuals with comorbidities or chronic illnesses such as chronic heart diseases, diabetes mellitus, chronic kidney diseases and blood disorders 5. individuals with weak immune system including cancer, HIV/AIDS, undergoing chemotherapy/on long-term steroids or organ transplantation 6. geriatric patients of more than 65 years of age with chronic illnesses 7. paediatric patients of less than 6 months of age 80 paediatric patients with comorbidities/chronic illnesses